DISTRIBUTION OF SURFACE CONDITIONS OF ICE SHEET IN ENDERBY LAND AND EAST QUEEN MAUD LAND, EAST ANTARCTICA - フルカワ, テルオ; ワタナベ, オキツグ; セコ, カツモト; フジイ, ヨシユキ; FURUKAWA, Teruo; WATANABE, Okitsugu; SEKO, Katsumoto; FUJII, Yoshiyuki (National Institute of Polar Research, 1992)
P(論文) Data on surface features collected by the Japanese Antarctic Research Expedition (JARE) along traverse routes were compiled to understand their aerial distribution in Enderby Land and East Queen Maud Land. This area can be divided into three regions on the basis of the regional characteristics of surface features. The results will be useful for deducing the aerial distribution of surface features from satellite images. departmental bulletin paper